Joseph Moiseevitch Tchaikov. De la Ruche des Makhmadim à l’idéologie soviétique (1910-1937) - Marie Vacher (Les Cahiers de l'École du Louvre)
The reliefs decorating the propylaea of the Soviet pavilion at the 1937 Exposition Internationale in Paris were recently rediscovered on French soil, along with their sculptor, Iosif Chaykov (1888-1979). The study of Chaykov’s oeuvre raises the question of the relationship between art and ideology, while enabling us to grasp the complexity of the Russian avant-garde between about 1910 and 1930, well beyond the usual limits. Making his formal experiments a quest for identity, Chaykov defied classification. With him, La Ruche was no longer that of Chagall and Soutine, but a laboratory for the creation of a “Jewish style in the visual arts”. The Yiddish avant-garde found its place within the Russian avant-garde, and the “super-eclecticism” of Jewish art defined by Abram Efros became the means of attaining the universal.